PERLINDUNGAN BAGI KONSUMEN TERKAIT PENCANTUMAN KLAUSULA PEMBATASAN RENOVASI RUMAH DALAM PERJANJIAN PENGIKATAN JUAL BELI PERUMAHAN PADA PT.BANGUN RIAU CENDIKIA (PT. BRC) DI PEKANBARU - TAUFIK MUSLIM (PREMISE LAW JURNAL, 2016)
The implementation of the clause on house renovation restriction in housing purchase agreement that are made by developer using standard contracts is that they have to firstly prepare the agreement in written form as well as for the clause of the article in housing purchase agreement. This objective of the study was to determine the rights and obligations of the developer, PT. BRC (Limited Liability Company of Bangun Riau Cendikia), toward PT. BRC consumers as the buyers who had lived in Vila Cendikia Cluster. This study entitled Protection for Consumers in the Inclusion of Clause on House Renovation Restriction in Housing Purchase Agreement at PT. Bangun Riau Cendikia (PT. BRC) in Pekanbaru. It was an empirical judicial research.  It took 15 (fifteen) respondents representing the property buyers and residents. The results showed that the rights of property buyers were found to be imbalanced with the rights of PT. BRC developers due to the restriction resulted from the inclusion of clause on house renovation restriction stated in the PPJB (Housing Purchase Agreement) whereas reviewed from the Laws No. 8/ 1999 on Consumers Protection Article 1(8) Clause (1), the inclusion of standard clause is strictly prohibited for any businessmen who offered their products. Meanwhile, the inclusion of the clause on house renovation restriction harmed the consumers’ freedom to make renovations which have become more limited; the consumers had to get an approval from the developers of PT. BRC before renovating their houses. Keywords: Consumer Protection, Purchase Agreement, Developer